2015
DOI: 10.1007/978-3-662-46678-0_21
|View full text |Cite
|
Sign up to set email alerts
|

The Cyclic-Routing UAV Problem is PSPACE-Complete

Abstract: Abstract. Consider a finite set of targets, with each target assigned a relative deadline, and each pair of targets assigned a fixed transit flight time. Given a flock of identical UAVs, can one ensure that every target is repeatedly visited by some UAV at intervals of duration at most the target's relative deadline? The Cyclic-Routing UAV Problem (cr-uav) is the question of whether this task has a solution. This problem can straightforwardly be solved in PSPACE by modelling it as a network of timed automata. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…In Darbari et al , the drone must discover obstacles and predict their motion in order to cover a maximum area within the limited flight time while avoiding collisions. Several articles investigate the cyclic‐routing drone problem, in which drones fly back and forth to update information on the objects’ positions .…”
Section: Planning Drone Operationsmentioning
confidence: 99%
“…In Darbari et al , the drone must discover obstacles and predict their motion in order to cover a maximum area within the limited flight time while avoiding collisions. Several articles investigate the cyclic‐routing drone problem, in which drones fly back and forth to update information on the objects’ positions .…”
Section: Planning Drone Operationsmentioning
confidence: 99%
“…For example Equation (18) ensures that the travel in the upward (up) direction from i to j is zero unless i − 1 is less than or equal j. The travel from one square to its right square must be impossible for the up, down, and left directions and it is shown in Equation (21).…”
Section: Modelmentioning
confidence: 99%
“…Based on the literature the UAV routing problem is also formulated as a VRP model where additional constraints need to be added to reflect the characteristics of the problem. UAV routing problem has attracted much attention in the past decade for different applications [17,18]. CPP, tries to find an appropriate path for robots while covering the pre-defined nodes.…”
Section: Introductionmentioning
confidence: 99%
“…In [3] and [4], the Cyclic Routing problem of UAVs is formally defined and a lower-bound on the number of required UAVs is obtained. In [5], the authors have shown that the Cyclic Routing of UAVs problem is polynomial space PSPACE-complete. In [6], a flexible model that allows multiple UAVs to cooperatively search for targets, and using a method to efficiently store dynamic target location probability distributions is addressed.…”
Section: Introductionmentioning
confidence: 99%